Arguments to believe and beliefs to argue. Epistemic logics for argumentation and its dynamics - Yuste-Ginel, Antonio (UMA Editorial, 2022)
Arguing and believing are two skills that have typically played a crucial role in the analysis of human cognition. Both notions have received notable attention from a broad range of disciplines, including linguistics, philosophy, psychology, and computer science. The main goal of this dissertation consists in studying from a logical perspective (that is, focused on reasoning) some of the existing relations between beliefs and argumentation. From a methodological point of view, we propose to combine two well-known families of formalisms for knowledge representation that have been relatively disconnected (with some salient exceptions): epistemic logic (Fagin et al., 2004; Meyer and van der Hoek, 1995) together with its dynamic extensions (van Ditmarsch et al., 2007; van Benthem, 2011), on the one hand, and formal argumentation (Baroni et al., 2018; Gabbay et al., 2021), on the other hand. This choice is arguably natural. Epistemic logic provides well-known tools for qualitatively representing epistemic attitudes (belief, among them). Formal argumentation, on its side, is the broad research field where mathematical representations of argumentative phenomena are investigated. Moreover, the notion of awareness, as treated in the epistemic logic tradition since Fagin and Halpern (1987), can be used as a theoretical bridge among both areas. This dissertation is presented as a collection of papers [compendio de publicaciones], meaning that its main contributions are contained in the reprint of six works that have been previously published, placed in Chapter 4. In chapter 1, we pursue a general introduction to the research problem. Chapter 2 is devoted to the presentation of the technical tools employed through the thesis. Chapter 3 explains how the contributions approach the research problem. Chapter 5 provides a general discussion of results, by analysing closely related work. We conclude in Chapter 6 with some remarks and open paths for future research.
Keywords: Lógica epistémica; Universidad de Málaga - Tesis doctorales; Lógica; Racionalismo; Conciencia; Epistemic logic; Formal argumentation; Believes; Argument; Awareness